1067. Interferon-free Hepatitis C Treatment Increases Surrogates of Cardiovascular Disease Risk in Black Veterans. (31st December 2020) - Mathur, Poonam; Kaplan, Roman; Theppote, Amanda; Kottilil, Shyam; Wilson, Eleanor
Abstract: Background: Sustained virologic response (SVR) after hepatitis C virus (HCV) treatment with either Interferon (IFN)-based or IFN-free regimens with direct-acting antivirals (DAAs) has been shown to reduce cardiovascular disease (CVD) events in majority white populations stratified by ASCVD score. However, the effect of IFN-free therapy on lipid profiles after SVR, as an indirect measure of CVD risk, is unknown in Black patients. Methods: We evaluated HCV-infected Veterans from the Baltimore VA who were treated with DAAs between 2015-2019. We performed a retrospective analysis comparing lipid profile changes following SVR among those with early stage (F0-F2) fibrosis and advanced liver disease (ALD, F3-F4 fibrosis) using two-tailed paired t-tests. Independent t-tests were used to assess differences in lipid profiles based on fibrosis stage in patients with HIV and Type II Diabetes Mellitus (DM2). Results: Of those treated for HCV (n=1, 528), 96% (n=1, 474) achieved SVR. Demographics are shown in Table 1. Most patients were Black males (75%) and a minority (2.7%) received statin therapy during treatment (Table 1). Of 1, 094 patients for whom data was available, an increase in total cholesterol (TC) and LDL (p< 0.01 for both) was seen an average of 17 months after SVR, regardless of fibrosis stage (Figure 1). A significant decrease in triglyceride levels (p=0.04) was also seen in the ALD group after SVR (Figure 1). Mean pre-treatment HCV RNA level was comparable between fibrosis groups (F0-F2: 6.35 logs, F3-F4: 6.37 logs, p=0.46). There were 101 and 436 patients with HIV and DM2, respectively, for whom pre-treatment liver fibrosis data was available. In both groups, there were significant increases in LDL (p=0.008 (HIV), p=0.003 (DM2)) among patients with ALD following SVR. Table 1. Baseline characteristics of treated HCV-infected persons who achieved SVR. Figure 1. Mean lipid profile parameters before and after HCV treatment for patients who achieved SVR. TC was measured a mean of 8.1 months (228 days, SD 333 days) before treatment and 17.4 months (488 days, SD 196 days) after SVR. LDL was measured a mean of 8 months (224 days, SD 284 days) before treatment and 17.5 months (492 days, SD 201 days) after SVR. *=differences in means using paired t-test were statistically significant with p<0.05. HCV= Hepatitis C Virus, SVR= Sustained Virologic Response TC=Total Cholesterol, HDL= High Density Lipoprotein, LDL= Lipoprotein, TG= Triglycerides. Conclusion: In a cohort of mostly Black HCV-infected Veterans, significant increases in TC, driven by increases in LDL, were seen after SVR regardless of fibrosis stage. In addition, patients with ALD and HIV or DM2, who have an inherently higher risk of CVD, had increased LDL levels, suggesting that these patients should be screened and treated for HCV prior to development of ALD. Correlates such as the ASCVD score should be considered in the timing of HCV treatment, in order to reduce the long-term risk of CVD. Disclosures: Shyam Kottilil, MD PhD, Arbutus Pharmaceuticals (Grant/Research Support)Gilead Sciences (Grant/Research Support)Merck Inc (Grant/Research Support, Advisor or Review Panel member)